Lung ultrasonography in patients with COVID-19: comparison with CT. Issue 11 (November 2020) - Ottaviani, S.; Franc, M.; Ebstein, E.; Demaria, L.; Lheure, C.; Debray, M.P.; Khalil, A.; Crestani, B.; Borie, R.; Dieudé, P.
Abstract : AIM: To determine whether findings from lung ultrasound and chest high-resolution computed tomography (HRCT) correlate when evaluating COVID-19 pulmonary involvement. MATERIALS AND METHODS: The present prospective single-centre study included consecutive symptomatic patients with reverse transcription polymerase chain reaction (RT-PCR)-proven COVID-19 who were not in the intensive care unit. All patients were assessed using HRCT and ultrasound of the lungs by distinct operators blinded to each other's findings. The number of areas (0–12) with B-lines and/or consolidations was evaluated using ultrasound and compared to the percentage and classification (absent or limited, <10%; moderate, 10–25%; extensive, 25–50%; severe, 50–75%; critical, >75%) of lung involvement on chest HRCT. RESULTS: Data were analysed for 21 patients with COVID-19 (median [range] age 65 [37–90] years, 76% male) and excellent correlation was found between the ultrasound score for B-lines and the classification ( p <0.01) and percentage of lung involvement on chest HRCT ( r =0.935, p <0.001). In addition, the ultrasound score correlated positively with supplemental oxygen therapy ( r =0.45, p =0.041) and negatively with minimal oxygen saturation at ambient air ( r = – 0.652, p <0.01). CONCLUSION: The present study suggests that among COVID-19 patients, lung ultrasound and HRCT findings agree in quantifying lung involvement and oxygen parameters. In the context of the COVID-19 pandemic, lung ultrasound could be a relevant alternative to chest HRCT. Highlights: Ultrasonography is correlated with chest CT in COVID-19 patients. Lung ultrasonography could be a relevant alternative to chest CT. Lung ultrasonography is correlated with oxygen parameters.